2011
DOI: 10.2166/wst.2011.241
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low-cost cathode catalysts for high yield biohydrogen production in microbial electrolysis cell

Abstract: As an ideal fuel due to the advantages of no pollution, high combustion heat and abundant sources, hydrogen gas can be produced from organic matter through the electrohydrogenesis process in microbial electrolysis cells. But in many MECs, platinum is often used as catalyst, which limits the practical applications of MECs. To reduce the cost of the MECs, Ni-based alloy cathodes were developed by electrodepositing. In this paper hydrogen production using Ni-W-P cathode was studied for the first time in a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The Pt/MWNT cathode (surface area = 30 cm 2 ) was loaded with 0.5 mg cm −2 . Similar methods have been used for the preparation of MWNT cathode (0.5 mg cm −2 ) and Pt cathode (0.5 mg cm −2 ) using a platinum catalyst with a 5%(w/w) Nafion binder as described by Wang et al 14…”
Section: Methodsmentioning
confidence: 99%
“…The Pt/MWNT cathode (surface area = 30 cm 2 ) was loaded with 0.5 mg cm −2 . Similar methods have been used for the preparation of MWNT cathode (0.5 mg cm −2 ) and Pt cathode (0.5 mg cm −2 ) using a platinum catalyst with a 5%(w/w) Nafion binder as described by Wang et al 14…”
Section: Methodsmentioning
confidence: 99%
“…In another study, doping of biogenic Pd with Au was found to greatly alleviate the catalyst poisoning caused by sulfide and enable efficient dechlorination under environmental conditions. 47 For economic considerations, noble metals can be alloyed with non-noble elements 48 or even noble metal-free composite catalysts 49 can be created. For example, a Ti/nano-TiO 2 /Pd catalyst exhibited a comparable ORR catalytic activity with Pt and led to steady current generation when assembled in an MFC, with a maximum power density of 200 mW m À2 achieved.…”
Section: Characteristics Of Electrocatalystsmentioning
confidence: 99%
“…Walaupun Au dan Pt memiliki sifat logam yang berupaya meningkatkan prestasi BES, namun disebabkan kos yang tinggi menghalang aplikasi berskala besar dan tujuan pengkomersialan. Penggunaan Pt boleh memberi kesan negatif dan toksik kepada bakteria (Mustakeem 2015;Santoro et al 2018;Wang et al 2011).…”
Section: Ciri Bahan Elektrodunclassified